Puisi Indonesia Lombok: Perlawanan terhadap Hegemoni Tuan Guru - HD, Dharma Satrya (citeus, 2019)
This paper discusses Indoesian Lombok poem as a form of resistance toward Tuan Guru (master teacher) hegemony in Lombok. In 2000s, Tuan Guru achieved hegemonic position in Lombok. This paper uses the Gramsci hegemony theory because literary work is assumed to have hegemonic power. The result shows that the conception of Islam is formed in the story of Dewi Rengganis which tells the mixture of Arabic and Lombok Islam. Arabic Islam shows the aspects of form and Lombok Islam shows the substance. Tuan Guru comes with an orthodox Arabic discourse. The poem cleverly chooses the teacher as one way to make the public believe that the ideal teacher is Tuan Guru whose knowledge goes to the prophet. The concept was strengthened through the institutions of Nahdlatul Wathan and Pondok Pesantren. This pesantren boarding school education institution has made the hegemonic position of Tuan Guru last until now. Tuan Guru's hegemony reached its peak when the customs of shoving could be standardized into Islamic law. This pesantren boarding school education institution has made the hegemonic position of Tuan Guru last until now. Tuan Guru's hegemony reached its peak when the customs of sorong serah were standardized into Islamic law. It was in this context that Indonesian Lombok poetry was present to put up a fight against the discourse Tuan Guru. Finally, The poetry sorong serah, nyongkolan and pembayun elevated the discourse of tradition in discursive formation about Lombok.